Bioactivities and Mechanisms of Action of Sinomenine and Its Derivatives: A Comprehensive Review - Wen Hou; Lejun Huang; Hao Huang; Shenglan Liu; Wei Dai; Jianhong Tang; Xiangzhao Chen; Xiaolu Lu; Qisheng Zheng; Zhinuo Zhou; Ziyun Zhang; Jinxia Lan (Molecules, 2024)
Sinomenine, an isoquinoline alkaloid extracted from the roots and stems of Sinomenium acutum, has been extensively studied for its derivatives as bioactive agents. This review concentrates on the research advancements in the biological activities and action mechanisms of sinomenine-related compounds until November 2023. The findings indicate a broad spectrum of pharmacological effects, including antitumor, anti-inflammation, neuroprotection, and immunosuppressive properties. These compounds are notably effective against breast, lung, liver, and prostate cancers, exhibiting IC50 values of approximately 121.4 nM against PC-3 and DU-145 cells, primarily through the PI3K/Akt/mTOR, NF-κB, MAPK, and JAK/STAT signaling pathways. Additionally, they manifest anti-inflammatory and analgesic effects predominantly via the NF-κB, MAPK, and Nrf2 signaling pathways. Utilized in treating rheumatic arthritis, these alkaloids also play a significant role in cardiovascular and cerebrovascular protection, as well as organ protection through the NF-κB, Nrf2, MAPK, and PI3K/Akt/mTOR signaling pathways. This review concludes with perspectives and insights on this topic, highlighting the potential of sinomenine-related compounds in clinical applications and the development of medications derived from natural products.